Research on the path of practical cooperation between China and European Union countries under the environment of carbon neutrality and peak carbon dioxide emissions - Cai, Wangang (Frontiers in Ecology and Evolution, 2023)
Globalization is increasing daily with the development of the world economy and society. International conflicts, cooperation, and interdependence in international environmental relations have become increasingly prominent, laying a theoretical and practical basis for international environmental cooperation. The ecological protection industries of China and the EU (European Union) are facing great development opportunities. Many EU member states have advantages in developing the environmental protection industry, which facilitates all-around cooperation in the environmental protection industry with my country. Based on the target policy background of PCDE (peak carbon dioxide emissions) and CN (carbon neutrality) and domestic and foreign research, this paper proposes a study on the practical cooperation path between China and EU countries. Based on international input–output data, an economic output CDE (carbon dioxide emission) matrix is constructed to characterize countries’ economic and CDE correlation, thus forming a global CDE network. The analysis shows that the contribution rate of energy structure effect and energy intensity fluctuates slowly, indicating a positive and negative alternation; Our government should adopt an active energy optimization policy, speed up the formulation of macro policies such as carbon tax on energy-consuming industries, continuously optimize the energy structure and reduce the CDE intensity. By 2023, China’s unit GDP will remain the same by 40–50% compared with 2022. Furthermore, the practical cooperation path proposed in this paper can provide valuable insights for policymakers and stakeholders in both China and the EU to promote the development of the environmental protection industry and achieve the common goal of carbon neutrality. The findings of this study can be used to inform the design and implementation of policies and initiatives aimed at reducing carbon emissions, improving energy efficiency, and promoting sustainable economic growth. Additionally, the international CDE network constructed in this study can serve as a useful tool for monitoring and evaluating the effectiveness of environmental policies and initiatives at the international level. Overall, this paper contributes to the scientific understanding of the complex relationship between economic development and environmental protection and provides practical guidance for promoting international cooperation in the environmental protection industry.